Addressing complexities in MPM modeling of calibration chamber cone penetrometer tests in homogenous and highly interlayered soils. (June 2023) - Yost, Kaleigh M.; Martinelli, Mario; Yerro, Alba; Green, Russell A.; de Lange, Dirk A.
Abstract: Cone penetrometer tests (CPTs) are used to characterize soil for a variety of geotechnical engineering applications, including earthquake-induced liquefaction triggering assessment. Numerical modeling of CPTs is frequently used to better understand soil behavior, soil-penetrometer interaction, and engineering estimates made from CPT data. However, calibrating and validating numerical CPT simulations with experimental calibration chamber (CC) data can be challenging. Specifically, uncertainties in the interpretation of laboratory strength and compression data compound with uncertainties in the CC testing and the assumptions made when developing the numerical model. This article provides a comprehensive review of uncertainties in the calibration and validation of CPT numerical simulations performed in homogenous sand, homogenous clay, and layered sand-clay soil profiles, comparing numerical results with well-documented experimental calibration chamber tests performed at Deltares. In particular, the Material Point Method (MPM) is used to perform the numerical analyses. A framework is presented to assess how uncertainty in the numerical model output is attributed to each input parameter. It is demonstrated that uncertainties can be explored numerically. Finally, recommendations for future experimental and numerical studies of CPTs are provided.